Entre escrita, performance e negritudes femininas: trajetos e encontros possíveis - MOREIRA, Letícia Cardoso (2023)
The present work seeks to investigate how performatic writing helps in the production of subjectivity and expressiveness of black women, through writing workshops, where performative acts of the word occur, and in this process analyzing how memories occupy a space in these writings of themselves, as trajectories in performances of a majitarily subalternized and stigmatized group Representation that commonly departs from two poles: oppression and resistance, affecting in a certain way the complex relationship that intersects the concepts. In order to break with this logic and think about these subjects in a non-dichotomous way and to deal with the complexity of being a black woman in our society, I worked from Gloria Anazaldua's open letter. In order to base the axes of analysis, Gloria's notes (1980) will be used in a perspective of what it is to be an artist- writer, Kimlomba (2019) about memory as identity and; Paul Zumthor(2008) in the perspective of performance and orality, a concept widely experienced during these workshops, thinking about writing, performance, memory in an integrated perspective.